THE IMPORTANCE AND ROLE OF BEES IN PLANT POLLINATION (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Bees play an important role in plant pollination compared to wild insects. Bees live in large numbers (50-80 thousand), have the ability to collect large reserves of honey and pollen, and perform pollination by visiting a very large number of flowers. The worker bee lands on 100-150 flowers in each flight to the flowerbed, while the bees of the strong family land on 50-60 million flowers of sunflowers, alfalfa, melons, fruit trees, and other plants. During flowering, bees bring 3-5 million pollen grains in their bodies and successfully pollinate plants. Bees perform 80-90% of pollination work, while wild insects it pollinates up to 10-20%.